Museum Collections and the Importance of Studying History - Alturki, Hend Mohammed (Advances in Social Sciences Research Journal, 2020)
Generally speaking , museums reflect peoples civilizations, enhance patriotism , and play a vital role in serving culture and heritage .in addition, they monitor and document the history of nations and traditions of peoples through their cultural programs. They also provide an image of the cultural momentum and indicate how far the society is aware of the importance of historical documentation. From this perspective , museum visitors have the opportunity to be acknowledged with the cultures and civilizations of nations through their antiquity collections .